Legal Protection of Restaurant Franchise Brands, in the Perspective of Trademark Law and Islamic Law - Asti Wasiska; Adang Djumhur Salikin (Ann Publisher, 2025)
Background. Legal protection of restaurant franchise brands has a high urgency in the context of modern business developments in Indonesia. Trademarks, as legal and commercial identities, not only serve as differentiators but also as instruments that determine a business's sustainability and reputation. However, in practice, there are many trademark infringements in the form of imitation, unauthorized use, and manipulation that is detrimental to the original brand owner. Purpose. This study aims to examine the legal protection of restaurant franchise brands in the perspective of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, as well as from the standpoint of Islamic law that emphasizes the protection of property (ḥifẓ al-māl), justice, and the prohibition of fraudulent practices (tadlīs). Method. The research method used is a normative juridical approach, with a legislative, conceptual, and maqāṣid al-syarī'ah perspective. Result. The results of the study show that legal protection in the Trademark Law has provided a strong normative basis, but its enforcement practices still face challenges. Conclusion. From the perspective of Islamic law, the protection of restaurant franchise brands is well-founded because it aligns with the principles of safeguarding ownership rights, preventing tyranny, and supporting the sustainability of halal businesses. Implementation. The integration between positive law and Islamic law is vital to strengthen the protection of restaurant franchise brands in order to create legal justice and certainty of doing business.